Toksisitas dan Repelensi Minyak Sereh Dapur [Cymbopogon flexuosus (Nees ex Steud.) W. Watson] terhadap Kecoak Jerman (Blattella germanica L.) - Yana, Syafri; Rahayu, Resti; Mairawita, Mairawita (Metamorfosa: Journal of Biological Sciences, 2018)
The purposes of this study are to find out the toxicity and repellency of lemongrass oil ( Cymbopogon flexuosus )  to the German cockroach ( Blatella germanica ). Study was conducted from August to October 2016 in Research Laboratories of Animal Physiology, Department of Biology, Faculty of Mathematics and Natural Sciences Andalas University Padang. This study used the glass jar method (contact) with three strains of German cockroaches (VCRU-WHO, KRS-BDG and HHB-JKT) and lemongrass oil. The average of lethal time after 6 hour  exposure ware counted with a probit analysis until found value LC90. The results showed that based on value LC90 strain VCRU-WHO 15,20%, strain KRS-BDG 22,42% and strain HHB-JKT 19,28% after 6 hour  exposure.